Cardiovascular Risk Factors and the Risk of Discontinuation of Advanced Therapies Due to Treatment Failure in Rheumatoid Arthritis: Results From the Ontario Best Practices Research Initiative - Aboulenain, Samar; Li, Xiuying; Movahedi, Mohammad; Bombardier, Claire; Kuriya, Bindee (ACR open rheumatology, 2023)
Objectives Our goal was to investigate whether cardiovascular disease (CVD) risk factors are associated with the retention of biologic disease‐modifying antirheumatic drugs (bDMARDs) or targeted‐synthetic DMARDs (tsDMARDs) in patients with rheumatoid arthritis (RA). Methods We included participants in the Ontario Best Practices Initiative RA registry who initiated their first bDMARD or tsDMARD. Participants were grouped by the number of baseline CVD risk factors (0, 1, or ≥2). The primary outcome was time‐to‐discontinuation of therapy for any reason. Secondary outcomes included discontinuation for primary failure, secondary failure, or due to adverse events. Competing risks hazards model, adjusted for clinically important confounders, estimated the association between CVD risk factors and treatment retention. Results The sample included 872 patients, of which 58% (n = 508) discontinued their b/tsDMARD after a median of 13 months from the time of initiation. The most common causes for treatment discontinuation were primary failure (n = 72), secondary failure (n = 126), or adverse events (n = 133). Patients with no CVD risk factors experienced significantly longer treatment survival compared to patients with 1 or ≥2 CVD risk factors. In multivariable‐adjusted analysis, there was no association between all‐cause discontinuation and CVD risk factors. However, there was a significant association between the presence of >1 CVD risk factor and treatment discontinuation, notably due to secondary treatment failure, but not due to adverse events. Conclusion Multiple CVD risk factors increase the risk of treatment failure in RA, particularly for secondary treatment failure. To improve patient outcomes, future research should focus on developing strategies to identify early treatment nonresponse and investigate the potential modifiability of this association.